Conceptual framework for an episode of rehabilitative care after hip fracture surgery - Sheehan, K.J.; Smith, T.O.; Martin, F.C.; Johansen, A.; Drummond, A.; Beaupre, L.; Magaziner, J.; Whitney, J.; Hommel, A.; Cameron, I.D.; Price, I.; Sackley, C. (Oxford University Press, 2018)
Researchers face a challenge when evaluating the effectiveness of rehabilitation after hip fracture surgery. Reported outcomes of rehabilitation will vary depending on the endpoint of the episode of care. Evaluation at an inappropriate endpoint may suggest a lack of effectiveness leading to the underuse of rehabilitation that could improve outcomes. The purpose of this paper is to describe a conceptual framework for a continuum-care-episode of rehabilitation after hip fracture surgery. We propose definitions for the index event, endpoint, and service scope of the episode. We discuss challenges in defining the episode of care, operationalizing the episode, and next steps for researchers. The episode described is intended to apply to all patients eligible for entry to rehabilitation after hip fracture and includes most functional recovery endpoints. This framework will provide a guide for rehabilitation researchers when designing and interpreting evaluations of the effectiveness of rehabilitation after hip fracture. Evaluation of all potential care episodes facilitates transparency in reporting of outcomes enabling researchers to determine the true effectiveness of rehabilitation after hip fracture surgery.